2008
DOI: 10.1086/528985
|View full text |Cite
|
Sign up to set email alerts
|

Time Variability of Interstellar Scattering and Improvements to Pulsar Timing

Abstract: Delay due to multipath scattering in the interstellar medium is a concern for high-precision pulsar timing, particularly if it is not constant over time. We report on 36 weekly observations of the pulsar PSR B1737ϩ13 with the Arecibo telescope that monitored the time variability of the scattering delay. At a frequency of 1380 MHz, the interstellar delay varied between 0.2 and 2.1 ‫1.0ע(‬ ) over 270 days of observation. The delay ms ms was consistent over four observing bands with center frequencies from 1175 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 25 publications
(23 reference statements)
0
76
0
Order By: Relevance
“…The parameters of the pulsars in our sample are typical of those found in the PTAs, the only difference being their longer pulse periods. This suggests that the ISM may not cause as much of a hindrance to pulsar timing projects as first feared (Hemberger & Stinebring 2008).…”
Section: Ism Effectsmentioning
confidence: 83%
See 1 more Smart Citation
“…The parameters of the pulsars in our sample are typical of those found in the PTAs, the only difference being their longer pulse periods. This suggests that the ISM may not cause as much of a hindrance to pulsar timing projects as first feared (Hemberger & Stinebring 2008).…”
Section: Ism Effectsmentioning
confidence: 83%
“…This relation was used as early as 1968 to accurately predict the dispersive time delay to within 1 part in 3000 between 40 MHz and 430 MHz (Tanenbaum et al 1968). However, as ever higher timing precision is required for projects like using pulsars for gravitational wave detection (Jenet et al 2005) it is important that any second-order effects of the ISM, such as refractive delays, DM variations and delays associated with pulse broadening from scattering (Foster & Cordes 1990;Cordes & Shannon 2010), are also studied and understood fully (You et al 2008;Hemberger & Stinebring 2008). Most of these proposed effects have strong frequency dependencies, with scaling indices between ν −3 and ν −4 , and are therefore most prominent at low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Both the multipath scattering and dispersive effects are observed to change on timescales as short as one day and as long as decades (e.g. Kaspi, Taylor, & Ryba 1994;Cordes et al 1990;Hemberger & Stinebring 2008). This makes multifrequency 1 Green Bank Ultimate Pulsar Processing Instrument (at least two receivers, each with wide bandwidths, such that at least 4 separate frequency bands are accessible) observations a requirement at each epoch.…”
Section: Observationsmentioning
confidence: 99%
“…First recognized by Stinebring et al (2001) in Arecibo data, detailed studies of these arcs have revealed a variety and richness in their observational manifestations; e.g., forward and reverse arcs, and a chain of arclets (Hill et al 2005;Putney & Stinebring 2006;Brisken et al 2010), which also stimulated a great deal of theoretical and modeling work (Walker et al 2004;Cordes et al 2006;Brisken et al 2010). In the context of PTAs Hemberger & Stinebring (2008) measured scattering delays from their observations of scintillation arcs in PSR B1737+13 (DM=48.9 pc cm 3 -); the delays varied from ∼0.2 to 2 μs at a frequency of 1.3 GHz.…”
Section: Introductionmentioning
confidence: 99%